2007
DOI: 10.3402/ijch.v66i1.18226
|View full text |Cite
|
Sign up to set email alerts
|

Stress, coping, and well-being among the Yup`ik of the Yukon-Kuskokwim Delta: the role of enculturation and acculturation

Abstract: Objectives. To report on the relationships between cultural identity and stress, coping, and psychological well-being in Yup'ik communities. Study Design. A quantitative self-administered questionnaire. Methods. A health and wellness survey was completed by a total of 88 Yup'ik participants ( 8 women and 0 men) from 6 rural villages in the Yukon-Kuskokwim Delta region. Respondents were fairly equally distributed across an age range of 14 to 94 (mean ± SD = 38.50 ± 17.18). Results. Participants who reported liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 45 publications
2
61
1
Order By: Relevance
“…These outcomes move beyond the dominant body of quantitative research on enculturation as a buffer for adverse health outcomes, which has largely focused on individual-level indicators, such as stress (Walters & Simoni, 2002;Wolsko, Lardon, Mohatt, & Orr, 2007); alcohol and substance abuse (Currie et al, 2011;Fleming & Ledogar, 2008;Walters & Simoni, 2002;Whitbeck et al, 2004;Wolsko et al, 2007;Zimmerman et al, 1996); depressive symptoms (Bals, Turi, Skre, & Kvernmo, 2011;Fleming & Ledogar, 2008;Walters & Simoni, 2002;Whitbeck, McMorris, Hoyt, Stubben, & LaFromboise, 2002); suicidal ideation (Yoder, Whitbeck, Hoyt, & LaFromboise, 2006); externalizing behaviours (Bals et al, 2011;Fleming & Ledogar, 2008); and impacts of discrimination (Whitbeck et al, 2002;Whitbeck et al, 2004). In their research with the Maori, Houkamua, and Sibley (2011) found that while increased enculturation was associated with both increased individual well-being and decreased community well-being; however, their study illustrates the complexity of community health and wellness within a context of ongoing oppression and colonialism.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes move beyond the dominant body of quantitative research on enculturation as a buffer for adverse health outcomes, which has largely focused on individual-level indicators, such as stress (Walters & Simoni, 2002;Wolsko, Lardon, Mohatt, & Orr, 2007); alcohol and substance abuse (Currie et al, 2011;Fleming & Ledogar, 2008;Walters & Simoni, 2002;Whitbeck et al, 2004;Wolsko et al, 2007;Zimmerman et al, 1996); depressive symptoms (Bals, Turi, Skre, & Kvernmo, 2011;Fleming & Ledogar, 2008;Walters & Simoni, 2002;Whitbeck, McMorris, Hoyt, Stubben, & LaFromboise, 2002); suicidal ideation (Yoder, Whitbeck, Hoyt, & LaFromboise, 2006); externalizing behaviours (Bals et al, 2011;Fleming & Ledogar, 2008); and impacts of discrimination (Whitbeck et al, 2002;Whitbeck et al, 2004). In their research with the Maori, Houkamua, and Sibley (2011) found that while increased enculturation was associated with both increased individual well-being and decreased community well-being; however, their study illustrates the complexity of community health and wellness within a context of ongoing oppression and colonialism.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, self-esteem, subjective well-being, and social support from family and friends have also been shown to serve as protective factors that promote resilience among AI adults, college students, and adolescents (Bergstrom, Clearly, & Peacock, 2003;House, Stiffman, & Brown, 2006Montgomery, Miville, Winterowd, Jeffries, & Baysden, 2003;Powers, 2006;Stiffman et al, 2007;Whitesell et al, 2009;Wolsko, Lardon, Mohatt, & Orr, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers highlighted that the current study suggests that Yup'ik individuals generally link the acculturative process with negative health and stress while individuals who identified with their Yup'ik culture (i.e., traditions) view the enculturative process as a means of promoting health and overall well-being (Wolsko et al, 2007).…”
Section: Resilience Among American Indian Adults and College Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acculturation is closely associated with decreasing well-being and high levels of psychosocial stress among Alaska Natives , Wolsko et al 2007. A nutritional transition is occurring in indigenous communities throughout the Arctic, with severe implications for physical, as well as psychosocial health (Kuhnlein et al 2004).…”
Section: Methodsmentioning
confidence: 99%